Mass spectrometric analysis of digesta does not improve the allergenicity assessment of GM crops - Rod A. Herman; Patricia A. Bauman; Laurie Goodwin; Emir Islamovic; Eric H. Ma; Hector Serrano; Andre Silvanovich; Abigail R. Simmons; Ping Song; Afua O. Tetteh; Rong Wang (Transgenic Research, 2021)
An investigation of the potential allergenicity of newly expressed proteins in genetically modified (GM) crops comprises part of the assessment of GM crop safety. However, allergenicity is not completely predictable from a definitive assay result or set of protein characteristics, and scientific opinions regarding the data that should be used to assess allergenicity are continuously evolving. Early studies supported a correlation between the stability of a protein exposed to digestive enzymes such as pepsin and the protein’s status as a potential allergen, but over time the conclusions of these earlier studies were not confirmed. Nonetheless, many regulatory authorities, including the European Food Safety Authority (EFSA), continue to require digestibility analyses as a component of GM crop risk assessments. Moreover, EFSA has recently investigated the use of mass spectrometry (MS), to make digestion assays more predictive of allergy risk, because it can detect and identify small undigested peptides. However, the utility of MS is questionable in this context, since known allergenic peptides are unlikely to exist in protein candidates intended for commercial development. These protein candidates are pre-screened by the same bioinformatics processes that are normally used to identify MS targets. Therefore, MS is not a standalone allergen identification method and also cannot be used to predict previously unknown allergenic epitopes. Thus, the suggested application of MS for analysis of digesta does not improve the poor predictive power of digestion assays in identifying allergenic risk.

Trace metal and nitrogen concentrations differentially affect bloom forming cyanobacteria of the genus Dolichospermum - Laura T. Kelly; Marion Champeaud; Veronica Beuzenberg; Eric Goodwin; Piet Verburg; Susanna A. Wood (Aquatic Sciences, 2021)

New Zealand estuary benthic health indicators summarised nationally and by estuary type - Anna Berthelsen; Javier Atalah; Dana Clark; Eric Goodwin; Jim Sinner; Murray Patterson (New Zealand Journal of Marine and Freshwater Research, 2020)
Ecological data are often collected at small geographic scales. However, analysing data collectively over wider scales can reveal results and patterns not shown in the smaller‐scale data. We summarised data for intertidal benthic ecological (physico‐chemical and biological) health indicators from New Zealand estuaries and compared the results against thresholds above which ecological impacts are expected to occur. Values for the sediment physico‐chemical indicators mud and nutrients (nitrogen and phosphorus collectively) were above thresholds for at least 50% and at 31% of sites measured respectively. Sediment organic content and metal concentrations were generally low, with only maximum values exceeding the thresholds. Scores for biological indicators were within (or better than) the moderate health category for either at least 50%, or at least 75%, of sites. When compared across estuary types (based on a geomorphic classification system) we found statistically significant differences for thirteen of the sixteen indicators. Differences (among mean values) for highly significant results were relatively large compared to the range of values observed nationally for those indicators. However, the differences, except those for mud, were smaller than their respective ecological health threshold values. Our summary provides a reference for future comparisons of estuary indicators nationally and across estuary types.

Global Observational Needs and Resources for Marine Biodiversity - Gabrielle Canonico; Pier Luigi Buttigieg; Enrique Montes; Frank E. Muller-Karger; Carol Stepien; Dawn Wright; Abigail Benson; Brian Helmuth; Mark Costello; Isabel Sousa-Pinto; Hanieh Saeedi; Jan Newton; et al. (Frontiers in Marine Science, 2019)

Optimising conditions for growth and xanthophyll production in continuous culture of Tisochrysis lutea using photobioreactor arrays and central composite design experiments - Veronica Beuzenberg; Eric O. Goodwin; Jonathan Puddick; Donato Romanazzi; Serean L. Adams; Michael A. Packer (New Zealand Journal of Botany, 2017)
The production of valuable metabolites from microalgae represents a potentially sustainable source of a range of products that can be difficult to synthesise directly. Microalgae respond to the dynamic and often subtly shifting growth environment in a complex way. The optimal conditions for growth can be quite different to those needed for optimal product generation, depending on the nature of the biosynthesis of that product. This is especially so for secondary metabolites. A combination of a multi‐vessel photobioreactor array, where certain growth conditions can be monitored and controlled precisely together with an experimental design matrix has been used to determine the optimal combination of temperature, irradiance and pH for a group of xanthophylls including fucoxanthin in the algae Tisochrysis lutea in continuous culture. Continuous culture as a mode is more suited for industrial production than batch mode in which the media constituents and algal population change dramatically over time. The central composite design experiment matrix has a range of set values for each parameter being investigated that bracket the optimal conditions. The three parameters investigated in this work (temperature, irradiance and pH) are major factors influencing algal growth. The method can be applied to other parameters that might affect growth or might affect production of a metabolite of interest, such as a nutrient level. The combined approach has been used previously to indicate optimal growth conditions for biomass generation and this work is one of the first to apply it to the generation of an algal product of interest.

Identifying Catchment-Scale Predictors of Coal Mining Impacts on New Zealand Stream Communities - Joanne E. Clapcott; Eric O. Goodwin; Jon S. Harding (Environmental Management, 2016)

Quantifying a dynamic risk landscape: heterogeneous predator activity and implications for prey persistence - Eric M. Schauber; Matthew J. Connors; Brett J. Goodwin; Clive G. Jones; Richard S. Ostfeld (Ecology, 2009)
Spatial heterogeneity in predation risk can ameliorate impacts on prey populations, particularly for prey of generalists. Spatially heterogeneous risk implies the existence of refugia, and the spatial scale of those refugia and their persistence over time affect whether prey can avoid predation by aggregating therein. Our objective was to quantify the magnitude, spatial scale, and temporal persistence of heterogeneity in risk of predation by white‐footed mice ( Peromyscus leucopus ), an abundant generalist predator of gypsy moths ( Lymantria dispar ) and songbirds. We used track plates to measure white‐footed mouse activity at >170 trees in each of three forest plots in upstate New York during summers of 2003–2005. We quantified the mean and coefficient of variation of track activity among trees by fitting the beta‐binomial distribution to data from each plot and study period. We measured temporal persistence by disattenuated autocorrelation, and spatial scale by fitting exponential variograms. Mice were much less abundant in 2005 than the other two years, leading to lower overall track activity but higher coefficient of variation among trees. Mouse track activity at individual trees was positively autocorrelated between monthly study periods in 2003 and 2004, and even between the two years, whereas temporal autocorrelation in 2005 was much weaker. Track activity showed positive spatial autocorrelation over lag distances from ∼30 to >1000 m. These findings indicate that mouse activity, and hence risk to their prey, varies substantially in space at spatial and temporal scales that appear responsive to mouse population dynamics. The spatial scale and temporal persistence of that variation imply that prey may benefit from returning to, or failing to disperse from, refugia.